Study on the Effect of Nozzle Angle and Air Flow Rate during Nanofluid Minimum Quantity Lubrication Milling of Aerospace Alloy Al7075-T6 - Harshit B. Kulkarni (Novel Perspectives of Engineering Research Vol. 10, 2022)
Present day industries are focusing on identifying various methods and techniques to implement sustainable manufacturing, which is ‘the need of the hour’. With the rise of global competition, industries are working hard to reduce machining costs, which are a major contributor to an industry’s’ manufacturing cost per part.’ The traditional approach of cooling the machining zone with excess use of coolant/cutting fluids at a rate of several liters per hour is raising a lot of concern. Industries must replace flood-coolant assisted machining with innovative procedures such as, the ’Minimum Quantity Lubrication’ (MQL) coolant supply methodology owing to strict government regulations. The objective of this research was to study the feasibility of replacing conventional flood cooling by a new technique called as Minimum Quantity Lubrication cooling. The work focused to investigate the effect of variation of nozzle orientation angle and air-flow rate, during MQL milling of aerospace aluminum Al7075-T6 alloy, using uncoated carbide tool. Dry, MQL, and nanofluid MQL (nanoparticle suspended oil with MQL) are the three methods of coolant supply that have been tested. As process variables, cutting speed [150 m/min, 208 m/min, 264 m/min], feed rate [95 mm/min, 110 mm/min, 125 mm/min], and depth of cut [0.5 mm, 1.3 mm, 2 mm] are used. With 1.5 kg/cm2 and 3 kg/cm2 air flow rates, two nozzle angles of 25° and 50° were investigated. The best results were achieved at a 1.5 kg/cm2 air flow rate. The ideal nozzle angle was discovered to be 250 degrees. Nanofluid MQL machining is a viable solution for achieving the lowest temperature and generating the least amount of heat. In terms of MQL approach, nanofluid MQL technology is used to get a better surface finish with reduced workpiece surface roughness (Al7075-T6).